2021
DOI: 10.1177/1553350621998871
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Measures in Colorectal Surgery: Construction of Core Measures Using Open-Source Research Method

Abstract: Purpose. The primary aim of the study was to review the existing literature about patient-reported outcome measures (PROMs) in colorectal cancer and IBD. The secondary aim was to present a road map to develop a core outcome set via opinion gathering using social media. Method. This study is the first step of a three-step project aimed at constructing simple, applicable PROMs in colorectal surgery. This article was written in a collaborative manner with authors invited both through Twitter via the #OpenSourceRe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…PROMs as subjective endpoints are mostly assessed through surveys. Nevertheless, an increasing number of studies address PROMs to standardize and validate these outcome measures such as the recent description from the #OpenSourceResearch collaborative of a general-psycho-physical score as a core outcome after colorectal surgery [ 23 ]. Regarding PREMs, their relation to surgical outcomes and PROMs is more subtle.…”
Section: Discussionmentioning
confidence: 99%
“…PROMs as subjective endpoints are mostly assessed through surveys. Nevertheless, an increasing number of studies address PROMs to standardize and validate these outcome measures such as the recent description from the #OpenSourceResearch collaborative of a general-psycho-physical score as a core outcome after colorectal surgery [ 23 ]. Regarding PREMs, their relation to surgical outcomes and PROMs is more subtle.…”
Section: Discussionmentioning
confidence: 99%
“…To retrieve data, PD codes were used as these are registered accurately in radiology departments. Third, the authors did not have information about CD activity and patients’ reported outcome measures, which are important in evaluating any outcome after surgical interventions 22 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Eagle study, conducted by the ESCP cohort studies committee, used clustered, randomized controlled trial design, while #OpenSourceResearch collaboration researched PROMs in colorectal surgery and implemented the principle of crowd science on the Twitter platform. 27 Despite this, surgical research can be difficult even in centers with well-developed infrastructure. Many of the challenges in surgical research relate to the fact that surgical procedures are complex health care interventions that are inter-and intraoperator dependent, meaning that "unlike 20-milligram tablets, no 2 surgical procedures are the same.…”
Section: Discussionmentioning
confidence: 99%
“…The paper was recently published in a surgical journal. 27 The interested reader is referred to supplementary files about Twitter interactions and the log file showing these discussions.…”
mentioning
confidence: 99%
See 1 more Smart Citation